Potential of the HSP70 protein family as biomarker of Crassostrea virginica under natural conditions (Ostreoida: Ostreidae) - Camarena-Novelo, Ingrid (2019)
The HSP70 proteins are used as exposure biomarkers, and the oyster Crassostrea virginica is considered as a bioindicator organism in environmental assessment. According to the season, the level of expression of the HSP70 family in wild oysters has not been characterized before. The aim of this work was to analyze the expression of the HSP70 family as an exposure biomarker using C. virginica gills from individuals and groups of oysters from the Tampamachoco Lagoon under natural conditions. Ninety oyster samples were collected at locations from the Tampamachoco Lagoon during the dry and “north winds” seasons. One group of oysters was maintained under laboratory conditions and exposed to thermal stress. The pH, temperature, salinity, and dissolved oxygen (DO2) were measured inside the brackish Tuxpam-Tampamachoco system. Salinity and DO2 were outside the limits recommended for brackish systems in both seasons. The electrophoresis and immunodetection assay of HSP70 were performed using proteins from oyster gills. The HSP73, HSP72 and HSP69 isoforms were expressed in dry season tissue samples, while only the HSP73 and HSP72 isoforms were detected in north winds season tissue samples and positive control tissue samples. The HSP73 isoform has not been previously reported in C. virginica. To evaluate the expression of HSP70 protein family at individual and group levels from wild animals, it is also important to determine a seasonal baseline expression.